How Justice Systems Realign in California: The Policies and Systemic Effects of Prison Downsizing, 1978-2013 - Petersilia, Joan ([Verlag nicht ermittelbar], 2017)
These data are part of NACJD's Fast Track Release and are distributed as they there received from the data depositor. The files have been zipped by NACJD for release, but not checked or processed except of the removal of direct identifiers. Users should refer to the accompany readme file for a brief description of the files available with this collections and consult the investigator(s) if further information is needed. The California correctional system underwent a dramatic transformation under California's Public Safety Realignment Act (AB 109) in 2011, a law that shifted from the state to the counties the responsibility for monitoring, tracking, and incarcerating lower level offenders previously bound for state prison. Realignment, therefore, presents the opportunity to witness 58 natural experiments in the downsizing of prisons. Counties faced different types of offenders, implemented different programs in different community and jail environments, and adopted differing sanctioning policies. This study examines the California's Public Safety Realignment Act's effect on counties' criminal justice institutions, including the disparities that result in charging, sentencing, and resource decisions.